Comparison of the temperature‐ and pressure‐dependent behavior of the crystal structure of CrAs. Issue 4 (27th July 2021) - Eich, Andreas; Grzechnik, Andrzej; Paulmann, Carsten; Müller, Thomas; Su, Yixi; Wolf, Thomas; Friese, Karen
Abstract : The dependences of the crystal structure of CrAs on temperature (30–400 K) and on pressure (0–9.46 GPa) are reported. The investigation shows twinning accompanying the temperature‐induced isosymmetrical phase transition and the existence of a distinct Cr–Cr distance within the structure showing anomalous behavior. Abstract : The crystal structure of CrAs was investigated using synchrotron X‐ray single‐crystal diffraction for separate dependences on temperature (30–400 K) and on pressure (0–9.46 GPa). The isosymmetrical magnetostructural phase transition at T N = 267 K can induce a change in the microstructure by twinning due to a crossing of the orthohexagonal setting of the unit‐cell parameter ratio c / b . Within the crystal structure, one particular Cr–Cr distance exhibits anomalous behavior in that it is nearly unaffected by temperature and pressure in the paramagnetic phase, which is stable above 267 K and at high pressures. The distinction of this shortest Cr–Cr distance might be of importance for the superconducting properties of CrAs.